Juridical Study Of Planning Murder Cases (Study Decision Number 91PID.B2022PN KRW) - Pahlepi, Hendra; Amaliya, Lia; Dewi, Sartika (Universitas Muhammadiyah Sumatera Utara, 2024)
Crime is someone's behavior that violates positive law or law that has been legitimized in force in a country. In this case premeditated murder is the crime of taking the life of another human being, or killing, after planning the time or method, with the aim of ensuring the success of the murder. The problem is how the juridical aspects relate to the handling of premeditated murder cases and how the judge considers them when deciding on murder cases in Decision Number 91/Pid.B/2022/Pn.Krw. Qualitative Research Method using the Normative Juridical approach method. The results of the research are the Juridical Aspects of the Elements of the Crime of Premeditated Murder, which are stated in article 340 of the Criminal Code: